Malaysia My Second Home (MM2H): Retirees' demographic profile and spending dynamics - Wong, Brian Kee Mun; Musa, Ghazali (Elsevier, 2017)
While most of the second home retirement tourism studies are qualitative in nature, knowledge on retirees' demographic profile and their spending dynamics is limited. We sampled Malaysia My Second Home (MM2H) participants at multiple data collection points, and received 504 usable completed questionnaires for analysis. The majority of the participants (56.3%) are aged between 60 and 69 years, mainly from Japan, the UK, and Australia. Their favourite residential locations are Klang Valley, Penang, Langkawi, Sabah, and Sarawak. Most of them stay about 10–12 months yearly in Malaysia, and spend an average of RM 6030 a month. Based on the recorded 29,390 second home participants, we calculate the potential direct spending contribution from MM2H participants to the Malaysian economy as RM 1.68 billion a year. We propose some marketing and managerial recommendations.